A Reading of the Poem al-Munājāh by Shaykh Zakariyya al-Anṣārī: A Prospective Theoretical Study on Students of Ma’had Dār al-‘Ulūm Banyuanyar, Pamekasan, Madura - Samsul AR; Turmudzi Turmudzi; Shulhan Shulhan; Syarifah Syarifah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2023)
It is customary for the students of the Darul Ulum Banyuanyar Islamic Boarding School to read the poetry of Zakiaria Al-Ansori after the fardu prayer. The verse is read repeatedly by the students. This is interesting for research to examine how students respond when reading these poems. Of course the poems that are recited have an impact on the santri themselves in the form of peace of mind, sharing, and blessings. To produce data, researchers used observation techniques, interviews and documentation. The results of this research show that some of the respondents when reading the poem did not make an impression and only as ordinary reading, of course, due to ignorance of the poem. So by knowing the meaning, the respondent will be able to absorb the poetry reading which is done after the five daily prayers. This research is a field research with a reception aesthetic approach.